Stability and Antiaging Effectiveness Studies of Astaxanthin-Loaded Nanostructured Lipid Carriers Using a Combination of Cetyl Palmitate and Soybean Oil - Zhihrotulwida, Dzakiya; Soeratri, Widji; Erawati, Tristiana; Rosita, Noorma (Research Center of Inorganic Materials and Coordination Complexes, FMIPA Universitas Sriwijaya, 2025)
Astaxanthin is a potent antioxidant belonging to carotenoid compounds that is mainly produced from green microalgae Haematococcus pluvialis. Astaxanthin is beneficial for skin health as antiaging agent, but has limitations in its delivery through the skin. Astaxanthin could be formulated in nanostructured lipid carriers to improve its efficacy. The purpose of this study was to evaluate the stability and antiaging effectiveness of astaxanthin-loaded nanostructured lipid carriers (ASX-NLCs) with cetyl palmitate and soybean oil as lipid combinations at several ratios of 100:0, 90:10, 80:20, and 70:30. ASX-NLCs were synthesized using a high-shear homogenization technique. ASX-NLCs were characterized and stability evaluated after storage for 90 days. The antiaging effectiveness of ASX-NLCs was evaluated by in vitro release test using dialysis bag for 8 hours, as well as collagen density and fibroblast count evaluation on UV-induced skin aging mice for 28 days. After storage, all ASX-NLCs did not change significantly in organoleptic, pH, and particle size. However, other parameters including polydispersity index, viscosity, and entrapment efficiency experienced significant changes in some formulas. The release test showed that F4 (70:30) gave the highest cumulative release and was significantly different from F1 (100:0). The collagen density of the groups treated with ASX-NLC F3 (80:20) and F4 (70:30) increased significantly compared to the UVB control group, while the fibroblast count did not differ significantly in all groups. Overall, ASX-NLCs containing cetyl palmitate and soybean oil at ratios of 80:20 and 70:30 could improve the antiaging effect of astaxanthin which might be influenced by its better stability and release.